Bullying di Sekolah: Pendekatan Multidispliner Melalui Perspektif Hukum, Pendidikan, dan Kesehatan - Hendra Harsanta; Rachmat Destriana; Ellysa Kusuma Laksanawati; Bambang Suhardi Waluyo (Jurnal Kemitraan Masyarakat, 2024)
Bullying in educational institutions poses a major problem that impacts various aspects of students’ lives, including their academic performance and mental well- being. This article explores oppression through legal, educational, and health perspectives while advocating multidisciplinary strategies to address it. By combining initiatives from these three areas, safer and healthier school environments can be fostered, as well as stronger support systems for those affected by bullying.